2012
DOI: 10.1111/j.2042-7158.2012.01484.x
|View full text |Cite
|
Sign up to set email alerts
|

In-vivo pharmacokinetics, tissue distribution and anti-tumour effect of hydroxycamptothecin delivered in oil-in-water submicron emulsions

Abstract: Submicron emulsions can alter the pharmacokinetic characteristics and tissue distribution of HCPT, and enhance tumour targeting and anti-tumour activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…Besides, it had been reported that positively charged nanorods were selectively accumulated in angiogenic endothelial cells of tumor; the ζ potential of HCPT NRs was 24.2 ± 0.7 mV, which may explain the high distribution of nanorods in tumor further. 44,45…”
Section: Resultsmentioning
confidence: 99%
“…Besides, it had been reported that positively charged nanorods were selectively accumulated in angiogenic endothelial cells of tumor; the ζ potential of HCPT NRs was 24.2 ± 0.7 mV, which may explain the high distribution of nanorods in tumor further. 44,45…”
Section: Resultsmentioning
confidence: 99%
“…H22 cells were removed from the abdominal cavity of a mouse within 9 to 11 d after inoculation. 8) In the experiment to assess the anti-tumour effect of HDE, H22 cells (1 × 10 6 ) were prepared by Hank's balanced salt solution and inoculated subcutaneously (0.1 mL) into the left axillary region of each mouse. When the tumour size reached to 4 to 6 mm, the experiment was initiated.…”
Section: Methodsmentioning
confidence: 99%
“…This was mainly due to the quick transport of 10-HCPT nanocrystals from the blood to organs such as the liver and spleen upon entering the circulatory system, which has been extensively reported. 21,30 The results presented in Table 3 showed that there were significant differences in the pharmacokinetic parameters between nanocrystals and injections groups. The elimination half-life of the 10-HCPT nanocrystals group was 2.98-fold as high as that of the injections group (P,0.001), and the area under the curve within 24 hours (AUC 0-24 ) value was 2.81-fold as high as the injections group.…”
mentioning
confidence: 97%